Gastrointestinal symptoms are predictive of trajectories of cognitive functioning in de novo Parkinson's disease. (March 2020) - Jones, Jacob D.; Rahmani, Elizabeth; Garcia, Erik; Jacobs, Jonathan P.
Abstract: Introduction: Non-motor symptoms such as cognitive and gastrointestinal (GI) symptoms are common in Parkinson's disease (PD). In PD, GI-symptoms often present prior to motor symptoms. It is hypothesized that GI-symptoms reflect disruptions of the microbiome-gut-brain axis, which leads to altered immune functioning, chronic neuroinflammation, and subsequent neurodegeneration. Initial evidence links gut-dysbiosis to PD pathology and motor symptom severity. The present study examines the longitudinal relationship between severity of GI-symptoms and cognitive impairment in newly diagnosed PD patients. Methods: A secondary data analysis of the Parkinson's Progression Markers Initiative (PPMI) included 423 newly diagnosed PD patients who were followed for up to 5 years. Participants underwent neuropsychological tests of processing speed, attention, visuospatial functioning, verbal learning and verbal delayed recall. Participant were classified as cognitive intact, mild cognitive impairment or Parkinson's disease dementia. Frequency of GI-symptoms were assessed with the Scales for Outcomes in Parkinson's Disease Autonomic (SCOPA-AUT). Multi-level models (MLM) examined the longitudinal relationship between GI symptoms and cognitive impairment. Results: All cognitive outcomes were predicted by the main effect of GI symptoms, or the GI-symptom X Occasion interaction term. Specifically, more severe GI-symptoms were predictive of a less favorable trajectory of performance on tests of letter fluency, visuospatial, learning and memory. Cognitive performance was uniquely associated with GI-symptoms and unrelated to non-GI autonomic symptoms. Conclusions: The presence of GI symptoms may serve as an early marker of cognitive impairment in PD. Future studies should examine specific mechanisms underlying the relationship between gut-dysbiosis and cognitive impairment. Highlights: Gastrointestinal symptoms are predictive of cognitive decline in early PD. MCI and PDD is more common among individuals with gastrointestinal symptoms. Gut-brain axis disruption may contribute to cognitive impairment.